2015
DOI: 10.1111/ppa.12327
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to a highly aggressive isolate of Sclerotinia sclerotiorum in a Brassica napus diversity set

Abstract: Sclerotinia stem rot (SSR) of oilseed rape (OSR, Brassica napus), caused by Sclerotinia sclerotiorum, is a serious problem in the UK and worldwide. As fungicide-based control approaches are not always reliable, identifying host resistance is a desirable and sustainable approach to disease management. This research initially examined the aggressiveness of 18 Sclerotinia isolates (17 S. sclerotiorum, one S. subarctica) on cultivated representatives of B. rapa, B. oleracea and B. napus using a young plant test. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 29 publications
(77 reference statements)
0
60
0
Order By: Relevance
“…As line 81 is a DH line, the resistance should be genetically fixed, which should allow a more straightforward route for introgression into B. napus . In resistance screen 2, lines 14 and 81 exhibited a significantly higher level of resistance in petiole tests than B. napus line 62, a line which was previously identified as the most resistant of 96 lines from a B. napus diversity set (line 69; Taylor et al ., ). To the authors’ knowledge, this is the first report of S. sclerotiorum resistance in B. cretica , which hence provides another potential source of useful breeding material.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…As line 81 is a DH line, the resistance should be genetically fixed, which should allow a more straightforward route for introgression into B. napus . In resistance screen 2, lines 14 and 81 exhibited a significantly higher level of resistance in petiole tests than B. napus line 62, a line which was previously identified as the most resistant of 96 lines from a B. napus diversity set (line 69; Taylor et al ., ). To the authors’ knowledge, this is the first report of S. sclerotiorum resistance in B. cretica , which hence provides another potential source of useful breeding material.…”
Section: Discussionmentioning
confidence: 97%
“…Using this test, only a single wild Brassica line (39, wild B. oleracea ) was significantly more resistant than the commercial B. napus cultivar Temple (line 57). Brassica napus line 59, which showed consistent resistance over the two leaf assays, also showed partial resistance in previous work using stem inoculation of mature plants (line 83; Taylor et al ., ). As observed in the petiole tests, some S. sclerotiorum resistance was also evident in B. incana lines using the leaf test, although a different line (line 17) was the most resistant.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…R.J. Snowdon, Bus et al 2011). UKVGB accessions have also been incorporated into a lettuce diversity set (Burns et al 2011), carrot diversity set (see Table 1), onion diversity set (see Table 1), and B. napus diversity set (Taylor et al 2015). Specific searches for publications using these research-derived resources were undertaken, and added to the group of publications identified previously.…”
Section: Research-derived Resourcesmentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t (Holst-Jensen et al 1998;Clarkson et al 2010Clarkson et al , 2013Clarkson et al , 2017Warmington 2014) and on vegetables such as bean, cabbage, carrot, celery root, Jerusalem artichoke, lettuce, pea, potato, pumpkin, rutabaga and turnip rape (Winton et al 2006;Warmington 2014;Norskog et al 2014;Brodal et al 2016;Clarkson et al 2017). This host range is still quite modest compared to that of S. sclerotiorum (more than 400 species, Boland & Hall 1994), but it is likely to continue increasing in future years, as suggested by infectivity tests carried out with S. subarctica isolates from meadow buttercup on additional plant species such as broccoli, canola and turnip (Clarkson et al 2010;Taylor et al 2015). …”
Section: Induction Of White Mould Symptoms On Witloof Chicory By S Smentioning
confidence: 99%